Investigating isomers/enantiomers of perfluorooctanoic acid in river water by gas chromatography–mass spectrometry with chiral derivatization. (January 2020) - Zhu, Jing; Harada, Kouji H.; Zou, Xiaoli; Sun, Chengjun
Abstract: Perfluorooctanoic acid (PFOA) in environmental media contains numerous isomers/enantiomers because of the PFOA manufacturing process and biological degradation of PFOA precursors. Few methods for analyzing PFOA enantiomers have been described. A simple derivatization method using (S)-1-phenethyl chloride that was developed to allow PFOA isomers/enantiomers to be separated by gas chromatography and analyzed by electron-capture negative ionization mass spectrometry is described here. PFOA standards were analyzed, and enantiomers of the chiral isomers perfluoro-3-methyl-heptanoic acid, perfluoro-4-methyl-heptanoic acid, and perfluoro-3, 5-dimethyl-hexanoic acid were separated using an HP-5MS column. Linear PFOA and perfluoro-6-methyl-heptanoic acid were chromatographically separated from these enantiomers. The linear ranges (giving correlation coefficients r > 0.997) of the calibration curves for the isomers were 0.010–3.00 ng/mL. PFOA isomer/enantiomer concentrations in river water were determined using the method. The method separated the enantiomers of perfluoro-3-methyl-heptanoic acid and perfluoro-4-methyl-heptanoic acid, the isomers of perfluoro-6-methyl-heptanoic acid, and linear PFOA in river water. No significant differences were found between the PFOA enantiomer/isomer compositions of the sample and technical PFOA. Enantiomer ratios can provide information about the sources and transport of pollutant isomers/enantiomers in the environment. Enantiomeric separation requires effective separation techniques. Our method achieved chiral separation using a non-chiral GC column that is often used in general analytical laboratories. The method could be used to investigate the sources and fates of PFOA and the isomers/enantiomers of other potentially toxic persistent pollutants in the environment and the risks posed to humans. Highlights: Derivatives of chiral PFOA enantiomers were separated using a non-chiral GC column. 3m-PFOA, 4m-PFOA, and 3, 5 dm-PFOA enantiomers were separated for the first time. Partial PFOA isomers and enantiomers were identified in river water.